KAJIAN TENTANG KEMAMPUAN SISWA TAHUN KEDUA DI SMAN 15 PEKANBARU DALAM MEMAHAMI TEKS HORTATORI EKSPOSISI - Ikke Oktavia S; Effendy Gultom; Masyhur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The students have to learn the four language skills. They are listening, speaking, reading, and writing. Reading plays an important role in learning. Reading is a communication process which requires a series of skills. Reading is actually a very complex process that requires a great deal of active participation on the part of the reader. The second year students of the senior high schools have learned some genres of reading texts From the researcher’s observation during her teaching practice, it was difficult for the students to comprehend English text. the researcher chose hortatory exposition as the text that is used for this research because they should learn hortatory exposition text. This research uses a quantitative method. The data for this research were obtained using an objective test. The result of the students scores in comprehending hortatory exposition texts can be described as follows : 6 students (13,95) were in excellent level, 24 students (55,81) were in good level, 10 students (23,25) were in medicore level, 2 students (4,65) were in poor level and 1 student (2,32) was in very poor level. The mean score of the students’ ability in comprehending hortatory exposition texts is 67,44. It can be stated that the students ability in comprehending hortatory exposition texts was in good level. Considering that the students’ ability level in terms of comprehending hortatory exposition text is classified into good level, but the students should learn more because only few of them achieve the standard minimum criteria (75,00) of their school. Keyword: Reading, Comprehension, Text, Hortatory Exposition Text